Implementasi Pendidikan Karakter melalui Pembelajaran IPAS Kelas 5 SD Negeri Cipondoh 2 Kota Tangerang - Aziz, Abdul; Zuliani, Rizki; Huliatunisa, Yayah (Universitas Muhammadiyah Magelang, 2025)
Education is a process of humanism referred to as an effort to humanize humans. Researchers discuss characters through science learning, namely independent, critical, and creative characters, to describe the implementation of character education through science learning for grade V. This study uses a qualitative descriptive approach. The subjects in this study were the Principal, 5th grade teachers, and 3 students. The research instruments used were observation, interviews, and documentation studies. Based on the results of the study, in accordance with observations, interviews, and analysis of document studies, it can be concluded that the application of character education as described from the results of interviews with 3 students who are representatives in this study. The application of characters in the aspects of independence, critical, and creativity, with their respective strengths. Student A excels in independence and collaboration, Student B stands out in quick responses and conveying ideas wisely, while Student C has strengths in mature thinking, open communication, and priority setting. Eachhas potential that continues to develop and requires different support to optimize their abilities.